Chemical composition of volatile oil of Thymus vulgaris L. from Western Ghats of India - A Stephen, S Ramesh, R R Rao, K V Syamasundar, B Srinivasulu, (Journal of Spices and Aromatic Crops, 2008)
The aerial parts of Thymus vulgaris collected from Western Ghats of India were analysed foressential oil by Gas Chromatography. Forty eight compounds were detected among which36 compounds, which constituted 98.63% of the oil were identified, with thymol (61.6%),p-cymene (11.2%), ϒ-terpinene (7.4%), methyl thymol (3.9%), methyl carvacrol (3.3%) andβ-caryophyllene (2.3%) as major chemical constituents.